Superconductivity in Te-deficient polymorphic MoTe2−x and its derivatives: rich structural and electronic phase transitions. (13th June 2018) - Kang, Se Hwang; Yu, Ho Sung; Baik, Jaeyoon; Yang, Heejun; Lee, Young Hee; Cho, Suyeon; Kim, Sung Wng
Abstract: The group 6 transition metal dichalcogenides (TMDs) have been received great attentions due to intriguing superconducting states correlated with structural uncertainty and electronic complexity. Here, we synthesized Te-deficient polycrystals of semimetallic MoTe2− x and its derivatives (Mo1− y TM y Te2− x Ch x ( TM : Nb, Mn and V, Ch : P)), and investigated the structural and electronic phase transitions. It was found that all Te-deficient semimetallic phases (monoclinic 1T′, hexagonal 2H and rhombohedral 3R) exhibited the superconducting transition, in which 2H and 3R structures were evolved in Nb-substituted Mo1− y Nb y Te2− x (y  =  0.4 for 2H, 0.6 for 3R), respectively. Moreover, we found that the superconducting state of 2H-and 3R-Mo1− y Nb y Te2− x appears at the vicinity of the transition from insulator to semimetal regime with the increased electron concentration via TM substitution and Te-deficiency. It is revealed that all superconducting 1T′-, 2H- and 3R-Mo1− y TM y Te2− x Ch x semimetals show the half-dome shaped superconducting phase diagram with respect to the electron concentration and TM substitution.